Dielectric and thermal properties of natural ester green nanofluids based on cottonseed oil for transformer applications - Farade, Rijavan (2021)
Vegetable oils have emerged as insulating fluids in transformer applications and as a prominent and effective alternative for traditional dielectric fluids. However, most vegetable oils are edible and their application is limited on a large scale. In the present work, a non-edible vegetable oil is developed as an insulating fluid. The developed oil is oxidation-inhibited cottonseed oil (CSO). Tertiary butylhydroquinone (TBHQ) was used as antioxidant. The concept of nanofluids was used to overcome the limited dielectric and thermal properties of base CSO. The used types of nanoparticles (NPs) were hexagonal boron nitride (h-BN) with 0.01 - 0.1 wt%, graphene oxide (GO) with 0.01 – 0.05 wt%, graphene with 0.0015 – 0.01 wt%, and Al2O3 NP with 0.01 - 0.05 wt%. Characterization of these NPs, methodology adopted for the preparation of nanofluids, and their stability into the prepared nanofluids were presented. GO was treated with sodium dodecyl sulfonate (SDS), graphene and Al2O3 with sodium dodecylbenzene sulfonate (SDBS) to obtain stable suspensions. The prepared nanofluids were tested for dielectric and thermal properties. The dielectric properties include breakdown voltages at room temperature and pressure; dielectric constant, dissipation factor, and resistivity at at 45 °C, 60 °C, 75 °C, and 90 °C; while thermal properties include thermal conductivity at 35 °C, 45 °C, 55 °C, and 65 °C; followed by thermal response and thermogram analysis. Few researchers investigated stability of dielectric nanofluids for use in transformers and adopted less effective qualitative visual inspection method. Also, relative permittivity models proposed earlier did not consider the interfacial zone created by surfactant. Therefore, three main objectives were aimed in this research; to develop non-edible CSO based nanofluids; to enhance dispersion stability, dielectric and thermal properties of CSO based nanofluids; and to design a relative permittivity model of nanofluids created by interfacial zone considering surfactant polarization. To attain the first objective, dielectric and thermal properties of CSO based h-BN and GO nanofluids were comprehensively evaluated. To attain the second objective, CSO based graphene nanofluids prepared with different sonication times were investigated for long-term stability through effective Ultraviolet-visible (UV-Vis) spectroscopy. Also, sonication time impact on dielectric and thermal properties were investigated. To attain the third objective, a polarization model of nanofluids was proposed to calculate relative permittivity considering surfactant effect. For the first objective, all the obtained results validated the superiority of CSO based h-BN and GO nanofluids as a potential candidates for power equipment. For the second objective, the presented results showed the relation between dispersion stability and thermo-dielectric properties, thereby contributed to long-term stability of CSO based graphene nanofluids. For the third objective, the results were discussed considering the structure of interfacial zone of CSO based Al2O3 nanofluids and the relative permittivity calculated from the model was almost in line with experimental results. In addition, for all the obtained results of the proposed nanofluids, corresponding physical mechanisms were discussed and clarified. Thus, dielectric and thermal properties investigation of proposed CSO based nanofluids open up a great opportunity in natural ester insulating fluid applications.